Market-oriented beekeeping development to improve smallholder income: Results of development experiences in Atsbi-Womberta District, northern Ethiopia - Woldewahid, G.; Gebremedhin, Berhanu; Hoekstra, Dirk; Tegegne, Azage; Berhe, Kahsay; Weldemariam, D. (International Livestock Research Institute, 2012)
Beekeeping is an important income-generating activity in the Atsbi-Womberta district of Tigray. Beekeeping can also be easily integrated into the on-going natural resources conservation developments in the district. However, beekeeping has traditionally been considered as a supplementary enterprise and its potential as a source of smallholder income has never been fully utilized. The Improving Productivity and Market Success (IPMS) of Ethiopian Farmers Project, in collaboration with the district Office of Agriculture and Rural Development (OoARD), the regional Bureau of ARD and other partners have introduced, tested and promoted improved beekeeping development practices based on the value chains framework. This paper presents results of this experience. The core of the experience is the transformation of a largely traditional system towards a more knowledge based and market-oriented beekeeping. Major interventions include introduction, testing and promotion of learning platforms on improved use of hive equipment, improved apiary and colony management, bee forages, harvesting and postharvest handling practices, and facilitation of access to market information and linkages. Qualitative and quantitative studies were conducted to assess developmental changes made due to the interventions. Results show that the honey productivity of adopters increased by about threefold (32 kg honey/hive per year) compared to the non-adopters (10 kg honey/hive per year) in 2008 despite the variation in rainfall distribution and amount. Interestingly, the honey productivity of adopters increased by 52% in 2008 (32 kg honey/hive per year) compared to those adopters in 2004 (21 kg honey/hive per year). Market-oriented improved beekeeping adopters had a threefold higher income from the sale of honey (Ethiopian birr, ETB1 1820/household per year) than non-adopters (ETB 614/household per year). Moreover, the gross annual income of smallholder beekeepers in the district increased from about ETB 2.7 million in 2004 to ETB 19.5 million in 2008. Similarly, the number of honeybee colonies has increased by about fourfold and that of beneficiaries increased by about threefold. About 36% of the beekeepers adopted improved beekeeping management which contributed to about 75% of the district gross annual income of smallholder beekeepers in 2008. The basis of transformation towards market-oriented beekeeping has been capacity building of beekeepers to acquire, share and use improved skills. Results show that marketoriented improved beekeeping appears to be a more resilient income generating business under the uncertain and variable rainfall conditions.